Learning from My Success and from Others' Failure: Evidence from Minimally Invasive Cardiac Surgery - KC, Diwas; Staats, Bradley R.; Gino, Francesca (Management Science, 2013)
Learning from past experience is central to an organization's adaptation and survival. A key dimension of prior experience is whether an outcome was successful or unsuccessful. Although empirical studies have investigated the effects of success and failure in organizational learning, to date, the phenomenon has received little attention at the individual level. Drawing on attribution theory in psychology, we investigate how individuals learn from their own past experiences with both failure and success and from the experiences of others. For our empirical analyses, we use 10 years of data from 71 cardiothoracic surgeons who completed more than 6,500 procedures using a new technology for cardiac surgery. We find that individuals learn more from their own successes than from their own failures, but they learn more from the failures of others than from others' successes. We also find that individuals' prior successes and others' failures can help individuals overcome their inability to learn from their own failures. Together, these findings offer both theoretical and practical insights into how individuals learn directly from their prior experience and indirectly from the experiences of others. This paper was accepted by Jesper Sørensen, organizations.